Garden Birds: How to Attract Birds to Your Garden - Proctor, Noble S.; Walker, Cyril Alexander; Parmenter, Tim (Rodale Press, 1986)
Includes a directory of 100 birds, describing their migration, habitat, scientific name, and physical characteristics.
Keywords: Bird attracting; Garden animals; dept.bio; faculty_collection

Academic-freedom - Smith, DG (Commentary, 1986)
tex.unique-id: ISI:A1986E898900011
Keywords: dept.bio; ⛔ No DOI found